Customer Relationship Management as a Development Challenge - Empirical Case Study in a Business to Business Relationship - Jokihaara, Minna (My University, 2005)
Customers are often a company’s most valuable asset in business to business markets. Therefore the management of customer relationships is an important factor on the success of a company. The purpose of this study is to assist a global engineering company to develop its customer relationship management within a relationship with a global terminal operator. For a company to be able to manage its customer relationships it must have a genuine understanding of what constitutes a business relationship. The theory of the study focuses first on the different elements of relationships. Then the management of business relationships is approached mainly from the International Marketing and Purchasing Group’s point of view, which emphasises the interaction processes of the relationships. The case relationship was studied by using the different elements and processes of relationships. The approach to the study is action research. The empirical data is gathered from the databases of the global engineering company, from publications of the industry and by interviewing the key persons of the global engineering company. Because of the unilateral point of view of the study the challenges in the development of the relationship are centred on issues the engineering company could improve unilaterally. The development challenges revealed by the study centred on the organisational culture, on the resource management and on managing the information exchange processes.
Keywords: Customer relationship management; business to business markets; substance of relationship; processes of relationship; fi=Markkinointi|en=Marketing|